DAKOCAN (Daun Kelobot Cantik): Pemanfaatan Limbah Kulit Jagung sebagai Aksesoris Fashion Bernilai Ekonomis - Bias Asmoroningtyas (INOTEKS : Jurnal Inovasi Ilmu Pengetahuan, Teknologi, dan Seni, 2022)
AbstractIn Indonesia, corn is only used as a staple food. Other parts of corn, such as cob and husk, are only used for animal feed, or even thrown away. In addition to reduce corn husk waste, this corn husk brooch products also aims to open up new jobs for the local community, especially for housewives and college students. The implementation method of this product includes three phases, namely the pre-production phase, the production phase, and the post-production phase. For marketing, until now the promotion of corn husk (klobot) brooch products has been carried out online and offline. Online promotion has been done through various social media, such as twitter, facebook, instagram, and whatsapp. For offline promotions, the brooch product has been marketed through endorsement of friends and relatives, sold in campus areas and the surrounding environment, and marketed through resellers, namely by entrusting products to be promoted and resold by other sellers through online and direct stores. Keyword: brooch products, cornhusk, kelobot